Telehealth for Goals of Care Conversations in Advanced CKD: A Mixed-Methods Pilot Study of US Veterans and Their Clinicians - Alexi Vahlkamp; Julia Schneider; Talar Markossian; Salva Balbale; Cara Ray; Kevin Stroupe; Seema Limaye (Kidney Medicine)
Rationale & Objective: Engaging patients with advanced chronic kidney disease (CKD) in goals of care (GOC) conversations is essential to align life-sustaining treatments with patient preferences. This pilot study described the feasibility of engaging older Veterans with advanced CKD in GOC conversations via telehealth by (1) comparing patient characteristics, including life-sustaining treatment note completion rates and preferences by visit modality, and (2) exploring Veteran and clinician perspectives surrounding telehealth GOC conversations. Study Design: Mixed-method convergent design including a prospective, quantitative observational cohort analysis (n = 40) and qualitative, semi-structured interviews with 4 clinicians and 11 Veterans. Descriptive statistics were used to describe the quantitative data. An inductive, rapid analytic approach and the constant comparison were used to analyze and interpret qualitative data. Quantitative and qualitative data were triangulated to identify practical suggestions to optimize GOC conversations via telehealth. Setting & Participants: Study participants included Veteran patients aged ≥70 years with advanced CKD stage 4 or 5 from a Veterans Affairs hospital nephrology clinic. Results: The cohort (n = 40) had a high probability of death, hospitalization, or both occurring within 90 days or 1 year. Across visit modalities, patient characteristics did not differ significantly. Two interrelated themes emerged from interviews: (1) GOC conversation feasibility varies by key personal and environmental factors (barriers and facilitators) across visit modalities, although overarching barriers include lack of non-palliative care provider engagement and uncertainty or lack of understanding surrounding illness trajectory, and (2) engaging Veterans in GOC conversations has a positive impact by creating a sense of reassurance regardless of visit modality. Limitations: The sample size was small (n = 40), and the study was unable to detect statistically significant differences in patient characteristics and clinical outcomes between visit modalities. Furthermore, future studies with larger and more diverse samples may be better equipped to identify differences by demographic characteristics. Conclusions: The findings suggest that it is feasible to engage older patients with advanced CKD in GOC conversations via telehealth, as patients wishing to complete a telehealth GOC conversation were able to. Factors increasing the ease of accessing GOC conversations may also increase their benefits, irrespective of visit modality. Plain-Language Summary: Goals of care (GOC) conversations for older patients with advanced chronic kidney disease (CKD) are important to align medical care with patient goals. Telehealth may be used to facilitate GOC conversations for these patients. We studied the feasibility of engaging older patients with advanced CKD in GOC conversations via telehealth. We compared demographic characteristics and visit outcomes between patients who completed telehealth versus in-person visits. We also interviewed patients and clinicians regarding their perspectives. The findings suggest that telehealth visits can be used for a select group of patients who prefer them to in-person visits. However, there are barriers and benefits with both modalities. There is no one-size-fits-all modality; rather, the needs of each patient should determine the most suitable visit modality.